126 Are we going in the same direction: do staff perceptions of their own and organisational goals align?. (16th November 2020) - Bullock, Stuart; Turner, Chris; Slowther, Anne
Abstract : Background: When we consider what the right thing to do is, we call upon our own morals, professional guidelines, the law and other perspectives. We often combine these with our perceptions of the desires of those in authority. This work aimed to unpack staff perceptions of organisational drivers and gain an understanding of how and where we strike the balance between these multiple (and sometimes conflicting) perspectives. Method: 'Sheila is in the Emergency Department (ED) waiting to be admitted to a bed with a higher level of monitoring. She is about to breach the 12-hour NHS target and a non-monitored ward bed has become available. You must decide whether or not she can be admitted.' 112 healthcare professionals were asked how they would respond to this scenario. They were asked if this was different to what they should do, and what they believed the department and trust management would like them to do. Results: 91% would keep the patient in ED and 96% felt their decision was also what they should do. Justifications were consideration of the patient's clinical needs and safety. 68% believed the department would like them to keep the patient in ED and this dropped to 27% when asked what trust management would like. The justifications for admitting the patient were avoiding a breach of targets and fears of hospital fines. Conclusion: This scenario saw participants abandon a target-based approach in favour of doing what they felt was right for a patient. For most there was a conflict between their actions and what they perceived those in positions of authority would want them to do. It is unlikely that those in managerial positions would willingly risk patient safety, but that appears to be the perception of frontline staff. Reductionist messages around targets have the potential to cause dissonance when the message competes with staff values. A more nuanced understanding of the drivers for all staff has the potential to reduce moral distress, a precursor of burnout.